2016
DOI: 10.1155/2016/8319542
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of Sago through Estate Plantation Scheme in Sarawak: The Way Forward

Abstract: Sago has been hailed as a next viable commodity in Sarawak, Malaysia, given its potential as a versatile crop. Realising its potential, Sarawak state government has started initiatives to stimulate sago plantation from subsistence farming to estate plantation. The move of introducing sago estate plantation is a bold one considering that Malaysia is the first country introducing such plantation design. This is a reflection on sago estate plantation in the state of Sarawak. It is observed that, in order to ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 3 publications
0
12
0
3
Order By: Relevance
“…Berdasarkan penelitian di Sulawesi Selatan, penjualan tepung sagu mengalami peningkatan signifikan pada Tahun 2006 -2013, yaitu sekitar 25% (Metaragakusuma et al 2017). Penggunaan sagu sebagai alternatif bahan pangan juga telah dilakukan di beberapa negara lain seperti Malaysia, melalui penanaman lahan sagu untuk komersialisasi (Chew et al 1998;Naim HM et al 2016).…”
Section: Hasil Dan Pembahasanunclassified
“…Berdasarkan penelitian di Sulawesi Selatan, penjualan tepung sagu mengalami peningkatan signifikan pada Tahun 2006 -2013, yaitu sekitar 25% (Metaragakusuma et al 2017). Penggunaan sagu sebagai alternatif bahan pangan juga telah dilakukan di beberapa negara lain seperti Malaysia, melalui penanaman lahan sagu untuk komersialisasi (Chew et al 1998;Naim HM et al 2016).…”
Section: Hasil Dan Pembahasanunclassified
“…Sedangkan kualitas pati sagu ditentukan oleh warna, viskositas, dan ukuran partikel (5) . Warna coklat di pati sagu dikarenakan adanya kandungan senyawa polyphenol (6) . Warna Sagu yang baik dan mempunyai nilai ekonomi yang tinggi adalah warna putih cerah dan tidak terdapat butiran warna hitam.…”
Section: Latar Belakangunclassified
“…On the other hand, this research found that the respond from smallholder farmers are rather slow. In order to speed up the process, it is suggested that communication between related agencies and smallholders need to improve in order to avoid miscommunication in message dissemination (Naim, Yaakub & Awang Hamdan, 2016). The sago logs produced by the Melanau communities are for their consumption, domestic markets and export.…”
Section: Income Generation and Access To Financial Resourcesmentioning
confidence: 99%